Too uncertain to consent, too supportive to refuse: the sociocultural dilemma of hesitant organ donors in Kazakhstan - Bolatov, Aidos; Asanova, Aruzhan; Abdiorazova, Aigerim; Pya, Yuriy (Frontiers in Public Health, 2025)
BackgroundUnderstanding the factors influencing posthumous organ donation decisions is essential for developing effective strategies to increase donor registration. While previous studies have explored reasons for consent and refusal, less attention has been given to individuals who defer the decision to their families (Decision Left to Close Relatives, DLCR). This study examines the sociodemographic, institutional, and cultural factors influencing donation preferences, with a focus on the DLCR group as a transitional category between consent (LC) and refusal (LR).MethodsA cross-sectional survey was conducted among 1,333 participants in Kazakhstan. Donation preferences were categorized into Lifetime Consent (35.3%), Lifetime Refusal (21.4%), and DLCR (43.4%). Participants completed measures assessing knowledge, attitudes, and perceived barriers to organ donation. Principal Component Analysis (PSA) identified two key dimensions of perceived barriers: institutional and cultural barriers. Linear regression and mediation analyses were performed to examine predictors of attitudes toward organ donation.ResultsThe DLCR group held intermediate attitudes toward donation, significantly higher than LR but lower than LC (p < 0.001), moreover, 44.4% of the DLCR group had a favorable attitude toward organ donation. A critical finding was the high level of uncertainty about how to declare donation status among DLCR participants, significantly higher than in both LC and LR (p < 0.05). PCA revealed that DLCR individuals were institutionally closer to LC but culturally aligned with LR, suggesting that cultural concerns are the stronger barrier preventing proactive consent. Among DLCR participants, knowledge positively predicted donation attitudes (β = 0.223, p < 0.001), while cultural and religious barriers had the strongest negative effect (β = −0.290, p < 0.001). Language preference also emerged as a factor, with Russian speakers demonstrating significantly more favorable attitudes than Kazakh speakers. Specialization (medical vs. non-medical) had no direct effect on donation attitudes (p = 0.777), but it influenced attitudes indirectly through institutional (β = −0.223, p < 0.001) and cultural barriers (β = 0.194, p = 0.003).ConclusionBoth procedural uncertainty and cultural-religious factors influence the hesitation of DLCR individuals to commit to donation, with cultural concerns having a stronger effect. Language preference also shapes attitudes, reflecting broader sociocultural framings. Reducing uncertainty and addressing cultural misconceptions, particularly among the DLCR group, may be key to increasing donor registration.